Xác định hàm lượng thủy ngân, đồng, cadmi, sắt, chì và kẽm trong một số nguồn nước ở tỉnh Phú Yên - Nguyễn, Giằng (Trường Đại học Đà Lạt, 2012)
More than 140 water samples from 7 differernce regions in Phu yen province are ananlysed for the elements. Cd. Cu. H g. Fe . Pb and Zn were determined by radiochemiscal neutron activation analysis(RNAA )and atomic absorption sectrophotomcter(AAS). Concentration of elements which were fequently analyzed ranged (in micro g/lit): Cd(0.24-0.8 4), Cu(10.1-58.7),H g (0.4 2 -0.9 5 ), Fe(80-6660), Pb(3.2-12.4) and Zn (28.8-78.6)